Problem-Based Learning to Enhance Environmental Awareness and Collaboration Among Elementary School Students - Kasmiati Kasmiati; Subuh Anggoro; Ristiana Dyah Purwandari (Journal of Social Research, 2026)
Environmental issues have become a growing global concern, making it essential to instill environmental awareness and collaboration skills in students from an early age. However, preliminary observations in several elementary schools in Kalimanah District, Purbalingga, revealed that science and social studies learning (IPAS) is still dominated by lecture-based methods, resulting in low student engagement, limited environmental awareness, and underdeveloped collaboration skills. This study aimed to investigate the effect of the Problem-Based Learning (PBL) model on environmental awareness and collaboration skills among fourth-grade elementary school students. The research employed a quantitative approach involving 60 fourth-grade students in Kalimanah District, Purbalingga, divided into an experimental group (PBL) and a control group (expository learning). Data were collected through environmental awareness questionnaires and collaboration skills observation sheets and analyzed using inferential statistics, including independent-sample t-tests and correlation analysis. The findings showed that the experimental group demonstrated significantly higher environmental awareness and improved collaboration skills compared to the control group. All indicators of environmental awareness—such as maintaining classroom and school cleanliness, caring for plants, supporting green programs, managing organic and non-organic waste, and maintaining sanitation facilities—improved substantially under the PBL model. Furthermore, active group interaction during PBL activities facilitated the development of collaboration skills, including shared responsibility, communication, and joint problem-solving. These results indicate that PBL effectively enhances students’ environmental attitudes and collaborative competencies through hands-on, contextualized, and meaningful learning experiences, offering both theoretical and practical implications for elementary science and social studies education.